FEMALE SEX WORKERS AND HIV/AIDS AWARENESS IN BAHAWALPUR, PAKISTAN - Jamal Abdul Nasir; Muhammad Imran; Fiaz Ahmad et al. (Journal of University Medical & Dental College, 2016)
OBJECTIVE: To assess the sexual behaviour and HIV/AIDS related knowledge among female sex workers (FSWs) in Bahawalpur division (BD). STUDY DESIGN: A cross sectional study. Setting: Three districts (Bahawalpur, Bahawalnagar and Rahim Yar Khan). DATA: Fifty FSWs from various brothels were interviewed by using convenient sampling. METHODS: Descriptive and inferential analysis carried out. RESULTS: Every 7 out of 10 FSWs were illiterate. Higher proportion (58%) of FSWs heard about HIV/AIDS but profound lack (66%) of comprehensive knowledge regarding HIV/AIDS transmission. The practice of consistent use of condom during sex remain quite low (32%) among FSWs and more than half (54%) of the respondents never asked to client for condom use before sex. Two models are executed separately to explore the association of FSWs knowledge about HIV/AIDS and comprehensive knowledge of HIV/AIDS. Age, education, marital status, duration as a sex worker, number of per month clients, consistent use of condom, sex service charge, asks client for condom use, multiple partner increases the chance of getting HIV, aware of sexually transmitted diseases (STDs) and mass media are found to be associated regarding comprehensive knowledge of HIV/AIDS transmission. CONCLUSIONS: FSWs were at high risk of contracting STDs and of transmitting it to their clients due to inconsistent condom use. Interventions are suggested to promote the comprehensive knowledge of HIV/AIDS and use of condom before sex, ultimately to improve health outcomes